Unlocking potential: Exploring the methane production potential in anaerobic co-digestion of cassava wastewater and glycerol - Devens, Kauanna Uyara; Ribeiro, Alexandre Rodrigues; Camargo, Franciele Pereira [UNESP]; Sakamoto, Isabel Kimiko; Varesche, Maria Bernadete Amâncio; Silva, Edson Luiz (Elsevier, 2024)
This study aimed at evaluating the feasibility of CH4 production in a mesophilic (30 °C) single-stage anaerobic co-digestion of cassava wastewater (CW) and glycerol in an anaerobic fluidized bed reactor (AFBR) with mixing ratio of 50 % / 50 % CW/Gly on a (chemical oxygen demand)COD basis. Thus, the following strategy was used: increasing the organic loading rate (OLR) (1–20 g COD.L−1.d−1) by increasing the substrate concentration (1–20 g COD.L−1) and applying a hydraulic detention time (HRT) of 24 h. The AFBR presented a maximum methane (CH4) content of 88.38±1.94 % and a CH4 yield (MY) of 293.48±18.37 mL of CH4.mL−1CODrem in the OLR of 1 g COD.L−1.d−1 and the maximum methane production rate (MPR) of 62.09±2.75 mL of CH4.L−1.h−1 in the OLR of 20 g COD.L−1.d−1. The conversion of glycerol and carbohydrates remained above 91±0.54 % and 82±2.79 %, respectively, and the COD conversion was above 80±0.65 %. The main metabolites were HAc, HPr, HBu, EtOH and HVa. The most abundant genera identified in the AFBR were Izemoplasmatales and Enterobacteriaceae for the bacteria domain, and Methanosaeta, Methanobacterium for the archaea domain. The single-stage system is robust and can operate with higher OLR without reducing the efficiency of wastewater treatment and CH4 production.
Keywords: Agro-industrial residues; Methanobacterium; Methanogenesis; Methanosaeta; Soluble metabolites